iMS‐Bmal1−/− mice show evident signs of sarcopenia that are counteracted by exercise and melatonin therapies - Fernández‐Martínez, José; Ramírez‐Casas, Yolanda; Aranda‐Martínez, Paula; López‐Rodríguez, Alba; Sayed, Ramy K. A.; Escames, Germaine; Acuña‐Castroviejo, Darío (Journal of pineal research, 2024)
Sarcopenia is an age‐related disease characterized by a reduction in muscle mass, strength, and function and, therefore, a deterioration in skeletal muscle health and frailty. Although the cause of sarcopenia is still unknown and, thus, there is no treatment, increasing evidence suggests that chronodisruption, particularly alterations in Bmal1 clock gene, can lead to those deficits culminating in sarcopenia. To gain insight into the cause and mechanism of sarcopenia and the protective effect of a therapeutic intervention with exercise and/or melatonin, the gastrocnemius muscles of male and female skeletal muscle‐specific and inducible Bmal1 knockout mice (iMS‐Bmal1−/−) were examined by phenotypic tests and light and electron microscopy. Our results revealed a disruption of the normal activity/rest rhythm, a drop in skeletal muscle function and mass, and increased frailty in male and female iMS‐Bmal1−/− animals compared to controls. A reduction in muscle fiber size and increased collagenous tissue were also detected, accompanied by reduced mitochondrial oxidative capacity and a compensatory shift towards a more oxidative fiber type. Electron microscopy further supports mitochondrial impairment in mutant mice. Melatonin and exercise ameliorated the damage caused by loss of Bmal1 in mutant mice, except for mitochondrial damage, which was worsened by the latter. Thus, iMS‐Bmal1−/− mice let us to identify Bmal1 deficiency as the responsible for the appearance of sarcopenia in the gastrocnemius muscle. Moreover, the results support the exercise and melatonin as therapeutic tools to counteract sarcopenia, by a mechanism that does not require the presence of Bmal1.